Analisis Kehadiran Siswa Sekolah Minggu Buddha Virya Dharma dalam Meningkatkan Pemahaman Ajaran Agama Buddha Sarana Puja - Sarwi Sarwi (Jurnal Budi Pekerti Agama Buddha, 2025)
This study aims to analyze the extent to which the attendance of students at the Virya Dharma Buddhist Sunday School contributes to an increase in their understanding of Buddhist teachings through the practice of puja facilities. Using a descriptive qualitative approach and supported by statistical attendance data, this study involved 15 students aged 1–17 years as respondents. Data were collected through observation, interviews, and documentation of activities. The results showed that students with high attendance rates tended to have a better understanding of the basic Buddhist values of puja facilities. Regular attendance also strengthened students' spiritual experiences through active involvement in puja, which encouraged the appreciation and application of Buddhist teachings in daily life. Thus, student attendance in Sunday school activities is not merely administrative, but becomes an important element in the formation of Buddhist character and spirituality from an early age.